Study of the Iberian inscriptions of the pottery vessel of the Ballesta Foundation, already known by a drawing and two fakes (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this work we analyse a painted pottery vessel that is preserved in the Ballesta Foundation, and that corresponds to the drawing we published in 2013. Once inspected, it is confirmed that the drawing only contains an error in a sign that coincides with a fracture. It should also be noted that in the last segment of the inscription of the side, an old correction is detected, which explains the strange shape of the second sign of the drawing. It is also especially significant to confirm that, as the drawing reflects, the two inscriptions use the duality of the trill, ŕ. This feature was not put in valuetill recently, and it is so subtle that it was not taken into consideration in the two forgeries. Thus, the characteristics of this inscription reinforce our initial hypothesis that this is an authentic artefact, since it is difficult to accept that a forger, especially in the 80’s, was capable of inventing two long and complex texts without any mistake. In addition, defending its falsity would entail defending the existence of two different teams of independent forgers, one skilled, which would not have acted again, and the other clumsy, responsible for most of the known fakes, circumstance in our opinion, absurd.
Keywords: Iberias lenguage